The repercussions of the Al-Aqsa flood on Saudi-American relations from the perspective of soft power (قضايا سياسية, 2023)
The Al-Aqsa Flood operation caused major changes in the balance of regional powers, and demonstrated a large aspect of the material tension between soft power and hard power. These events were reflected in the structure of international relations between the Arabs and the Zionist entity, and achieved many indicators at the level of Palestine and the Arab countries or at the Israeli level. To a greater extent, it affected the type and nature of relations between the Arab countries and the Zionist entity. At the forefront of those countries is the Kingdom of Saudi Arabia, for reasons that are continuing on the path of normalization similar to Egypt and other countries. Looking at the Kingdom of Saudi Arabia in this direction may explain a dialectic based on indicators of soft power. And hard power at the same time, which was also reflected in its relations with the United States of America.